2021
DOI: 10.15446/ga.v24n1.92479
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de bacterias y hongos aerotransportados por la lluvia horizontal de la región del Salto del Tequendama (Colombia)

Abstract: La contaminación del aire en ambientes externos puede ser considerada una vía de transmisión de agentes infecciosos que inducen enfermedades en animales, plantas y humanos. Por lo tanto, la evaluación de bioaerosoles en ambientes externos es importante para evaluar su impacto en el ambiente y en la salud humana. En este estudio se identificaron las bacterias y hongos aerotransportados presentes en el área del salto hidráulico de la región del Salto de Tequendama, con el fin de establecer la posibilidad de ries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…The bacterial strains isolated from the sampling area were related to the genera Staphylococcus, Bacillus, Enterococcus, Streptococcus and Pseudomonas. These results are comparable with other bioaerosol studies that have found the presence of these genera in different outdoor environments including coastal regions [11], urban environments [20][21][22], farms [23][24], landfills [25], and schools [26]. Staphyloccus spp.…”
Section: Correlation Of Meteorological Variables and Concentration Of...supporting
confidence: 90%
See 2 more Smart Citations
“…The bacterial strains isolated from the sampling area were related to the genera Staphylococcus, Bacillus, Enterococcus, Streptococcus and Pseudomonas. These results are comparable with other bioaerosol studies that have found the presence of these genera in different outdoor environments including coastal regions [11], urban environments [20][21][22], farms [23][24], landfills [25], and schools [26]. Staphyloccus spp.…”
Section: Correlation Of Meteorological Variables and Concentration Of...supporting
confidence: 90%
“…Species of the genus Staphyloccus are saprophytic, facultative aerobic, and colonize the surface of the skin and mucous membranes of humans and animals and are the causative agent of many severe acute and chronic infections [19]. The dominance of this genus in outdoor and indoor environments has been reported in previous studies [11] and [20][21][22][23][24][25][26], which is probably related to its ability to survive in unfavorable conditions, and because its presence in the environment increases through the skin, mouth, and nostrils. noses, human hair, and pets [26].…”
Section: Correlation Of Meteorological Variables and Concentration Of...mentioning
confidence: 89%
See 1 more Smart Citation